Difference in Vigilance Rates Between Harbor Seal (Phoca vitulina) Mothers with a Pup and Lone Adults - Furr, Hannah; Kurz, Gabriella (Friday Harbor Laboratories, 2014)
Knowing if rates of vigilance between mother harbor seals and lone adults (Phoca Vitulina) differ in any way is essential in moving conservation efforts in the right direction. We used focal individual and scan samples of harbor seals off of Yellow Island, WA to examine any possible differences in vigilance between the two seal categories at low tides. The result of overall vigilance rates for the seals was inconclusive. However, we did find that mother seals tend to be more vigilant the higher the tide goes, while lone adults had no change. This signifies that the less haul out space available, the more vigilant mothers become. Also, mothers spend less time loafing overall than lone adults and more time swimming, possibly due to the fact they are teaching their young feeding techniques. The data on vigilance rates being relatively equal between the two seal categories is inconsistent with prior studies, possibly due to smaller number of sample days. Overall, this study shows that while vigilance does not change much for mothers, they do spend more time exhibiting other active behaviors and less time resting than lone adults.